Micro-plasticity of genomes as illustrated by the evolution of glutathione transferases in 12 Drosophila species. - Saisawang, C.; Ketterman, A.J. (PLoS ONE, 2014)
Glutathione transferases (GST) are an ancient superfamily comprising a large number of paralogous proteins in a single organism. This multiplicity of GSTs has allowed the copies to diverge for neofunctionalization with proposed roles ranging from detoxication and oxidative stress response to involvement in signal transduction cascades. We performed a comparative genomic analysis using FlyBase annotations and Drosophila melanogaster GST sequences as templates to further annotate the GST orthologs in the 12 Drosophila sequenced genomes. We found that GST genes in the Drosophila subgenera have undergone repeated local duplications followed by transposition, inversion, and micro-rearrangements of these copies. The colinearity and orientations of the orthologous GST genes appear to be unique in many of the species which suggests that genomic rearrangement events have occurred multiple times during speciation. The high micro-plasticity of the genomes appears to have a functional contribution utilized for evolution of this gene family.